2021
DOI: 10.3390/ijgi11010011
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Identification of Addresses: A Systematic Literature Review

Abstract: Address matching continues to play a central role at various levels, through geocoding and data integration from different sources, with a view to promote activities such as urban planning, location-based services, and the construction of databases like those used in census operations. However, the task of address matching continues to face several challenges, such as non-standard or incomplete address records or addresses written in more complex languages. In order to better understand how current limitations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
1
3
0
Order By: Relevance
“…Cruz et al analyzed 41 papers on address matching published between 2002 and 2021 and discovered that most of the relevant studies have used deep learning methods. Among them, consistent with the above in this paper, due to the complexity of Chinese addresses, Chinese address matching accounted for half of the studies [37].…”
Section: Introductionsupporting
confidence: 87%
“…Cruz et al analyzed 41 papers on address matching published between 2002 and 2021 and discovered that most of the relevant studies have used deep learning methods. Among them, consistent with the above in this paper, due to the complexity of Chinese addresses, Chinese address matching accounted for half of the studies [37].…”
Section: Introductionsupporting
confidence: 87%
“…The tools are friendly and allow the digitization of aquatic systems in rural locations. Generally, address geocoding services are used in housing georeferencing processes; however, to georeference homes in rural locations without GPS cartography, mobile devices must be used [ 15 , 16 ]. This processing option involves the purchase of GPS devices and the transfer of personnel to the field to obtain the coordinates of each home.…”
Section: Discussionmentioning
confidence: 99%
“…The result showed that the proposed method gained a higher matching accuracy for unstructured address data, with its precision, recall, and F1 score up to 0.97. Another study [26][27][28][29][30][31] from related scholars also proposed different methodologies to deal with address-matching problems in various contexts by utilizing the most advanced technologies, such as deep learning and machine learning.…”
Section: Related Workmentioning
confidence: 99%